Follow me : Popular public memorials in Croatia - Cvetnić, Sanja (Array, 2007)
Follow me : Popular public memorials in Croatia Formally popular public memorials blend with a larger group of public crucifix or wayside shrine. But they differ in intention. Popular public memorials are erected in memory of the deceased members of community or family, particularly if the circumstances of death were tragic (such as young age of the deceased, violent death, or both). Popular public memorials come out of traditional popular culture. Therefore, the name, the glory and the importance of a single author (even though he/she is sometimes well-known) diminish in front of the intention of the collective to erect a memorial symbol, sign of its communed strength. Sometimes intentions overlap – popular memorials are erected both in memory of those who passed away and as an ex-voto of those who survived a war or some other menace. Popular public memorials are hidden in a greater net of public monuments of piety. Their “ official” life in Central Europe started in the end of the 16th century, in 1596, when Rudolph II the Habsburg decided to defend the imperial territory from the Turkish aggression with the sign of victory, the cross, since – as stated in his decision – the existing public crucifixes proved to be efficient in defense. After the Thirty Years War, ended with the Münster Peace in 1648, the crossroads in the German territories were to be marked by wayside shrines upon the order of Ferdinand III (1650), because – as he observed – the older public monuments, erected by Christian forefathers had been destroyed in the war turmoil. The intention of the two imperial edicts was to create visible and strong Catholic identity signs, even statements, in landscape. Popular religious memorials have multiple roles and meanings in the public space, such as being pastoral reminders to the sinners of the exalted example of the saints’ or the greatest, Christ’ s sacrifice. They are conveyors of the values accepted by one generation to their successors. After the First and Second World Wars, and the last, 1991-1995, new wayside shrines or public crucifixes in continental Croatia reveal inscriptions with consoling expressions of “ eternal memory” for the victims. These written ex-votos, added to the memorials, are addressed to various protectors and intermediators (mostly Virgin Mary), but rarely directly to God. Candles and flowers that are occasionally offered to public memorials thus honour both the saints (or Christ) and the memory of the deceased. Function of a public crucifix can be a very practical one – the patibulum of the memorial public crucifix in Donja Lomnica serves also as the pillar where notices of death are attached.